International Peace and Security in Maritime Domain - Isokaitė-Valužė, Indrė (Teisė, 2022)
The research aims at establishing which activities or situations in maritime domain, which threaten maritime safety and / or maritime security, fall within the concept of international peace and security. Having demonstrated the validity of the international law principles that safeguard international peace and security in maritime area, the research reveals a changing list of the threats to international peace and security, which now encompasses activities and situations at sea, including terrorism, sea piracy and armed robbery against ships, proliferation of weapons of mass destruction, etc. A maritime space safe from such kind of threats generally means maritime security. Thus, a great part of the threats to maritime security are or may constitute threats to international peace and security, subject to their recognition as such threats by the United Nations Security Council in its resolutions. Usually such threats also pose risk to maritime safety (safety at sea, safety of navigation, ships, crew and passengers); however, any threat to maritime safety does not necessarily endanger maritime security or amount to the threat to international peace and security.